Does Fiscal Decentralization Result in a Better Business Climate? - Sobel, Russell S.; Dutta, Nabamita; Roy, Sanjukta (Taylor and Francis, 2013)
Previous literature generally finds that greater fiscal decentralization is associated with faster economic growth, improved government performance and stronger constraints on the Leviathan behaviour of governments. Because economic growth critically depends on the presence of good government policies and institutions, the likely but untested link between these strands of literature is that greater decentralization probably improves growth because it results in government policies more conducive to entrepreneurship and business success. We test (and confirm) this hypothesis using several business climate measures for the US states.